1999
DOI: 10.1902/jop.1999.70.6.574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Initial Periodontal Therapy on the Frequency of Detecting Bacteroides forsythus, Porphyromonas gingivalis, and Actinobacillus actinomycetemcomitans

Abstract: These results indicate that initial conventional therapy can eliminate B. forsythus and P. gingivalis, but not A. actinomycetemcomitans. When levels of these bacteria decreased to below-detectable levels, clinical improvement was significant. These results indicate that monitoring levels of these three periodontopathic bacteria may render periodontal therapy more effective and accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(26 citation statements)
references
References 47 publications
3
19
0
4
Order By: Relevance
“…This study showed significant reductions in the quantity of P. gingivalis and T. forsythia in both groups following nonsurgical periodontal therapy while the level of A. actinomycetemcomitans was unaffected, which is in agreement with previous studies [3133]. Takamatsu et al [33] investigated the short-term effects of nonsurgical periodontal therapy on the quantity of P. gingivalis and T. forsythia in 26 periodontally diseased patients using DNA probe.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study showed significant reductions in the quantity of P. gingivalis and T. forsythia in both groups following nonsurgical periodontal therapy while the level of A. actinomycetemcomitans was unaffected, which is in agreement with previous studies [3133]. Takamatsu et al [33] investigated the short-term effects of nonsurgical periodontal therapy on the quantity of P. gingivalis and T. forsythia in 26 periodontally diseased patients using DNA probe.…”
Section: Discussionsupporting
confidence: 90%
“…Takamatsu et al [33] investigated the short-term effects of nonsurgical periodontal therapy on the quantity of P. gingivalis and T. forsythia in 26 periodontally diseased patients using DNA probe. The prevalence of A. actinomycetemcomitans was also identified, but, by using PCR, this study demonstrated significant reduction in the levels of P. gingivalis and T. forsythia while levels of A. actinomycetemcomitans were unaffected.…”
Section: Discussionmentioning
confidence: 99%
“…However, this therapy can often be challenged due to the complex and unfavorable radicular morphology, especially in sites of deep periodontal pockets 19 . In these cases, several studies have shown the presence of remnants of Tannarella forsythensis and mainly Aggregactibacter actinomycetemcomitans in periodontal pockets after non-surgical periodontal therapy 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Only methods that included intense scaling and prophylaxis followed by application of topical antiseptics allowed for sufficient microbial reduction to permit colonization of the newly implanted A. actinomycetemcomitans strains. These difficulties were not totally unexpected since the clinical literature is replete with indications regarding the difficulty clinicians have in removal and elimination of A. actinomycetemcomitans from the oral cavity of those infected with A. actinomycetemcomitans [1,3638]. Nevertheless, the intensity of the recolonization of native A. actinomycetemcomitans was surprising in light of the massive inoculation procedure we used to implant the “foreign” A. actinomycetemcomitans .…”
Section: Discussionmentioning
confidence: 99%